A Proposal on Techno-Financial Design aspects of Photovoltaic System for the Twin Districts of Rajouri and Poonch (Jammu & Kashmir) - Nabi Mughal, Shafqat; Raj Sood, Yog; Jarial, R.K. (EAI Endorsed Transactions on Energy Web, 2020)
In this paper, a procedural analysis involved in the optimal design of the photovoltaic system (PV) is thoroughly described. The study has been carried out by following a proposed design procedure, involving different types of photovoltaic panels and their tracking mechanisms. The proposed methodology is implemented in the twin districts of jammu & kashmir union territory (rajouri & poonch). The feasibility of the photovoltaic system has been made based on power output and the cost of generation. A detailed financial analysis is also carried out to find the levelised cost of electricity, amortisation time, and internal rate of return. This study will help the power utilities to mitigate their energy issues, by installing a photovoltaic system based on the proposed design methodology.